DISPOSABLE INCOME AND RELIGIOSITY AS DETERMINANTS OF INTEREST IN SAVING IN ISLAMIC BANKS - Bakhri, Syaeful; Hasanah, Syifa Nurul; Sukardi, Didi (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
The development of Islamic banking in Indonesia serves as a key indicator of the successful establishment and growth of Islamic financial institutions that operate under Sharia principles. As one of the countries with the largest Muslim population in the world, Indonesia holds great potential for the expansion of Islamic finance. In this context, understanding the behavioral factors that influence individuals’ interest in saving in Islamic banks becomes crucial. This study aims to examine the relationship between the level of disposable income and religiosity with the intention to save in Islamic banks. The research employs a quantitative method, using a structured questionnaire distributed to 43 employees of the Ministry of Religious Affairs in Cirebon City as the respondents.. The results indicate that both disposable income (X1) and religiosity (X2) have a positive and significant influence on saving interest (Y). This suggests that individuals with higher disposable income and stronger religiosity tend to be more motivated to save in Islamic banks. The findings of this study contribute to a better understanding of consumer behavior in Islamic finance and provide valuable insights for Islamic banking institutions in developing strategies to increase customer participation and loyalty.